Analisa Faktor Kepuasan Pasien di Rawat Inap RSIA Prima Qonita Kabupaten Ogan Komering Ulu Provinsi Sumatera Selatan - Rahmat Fikri; Christin Angelina Febriani; Nova Muhani; Samino Samino; Fitri Ekasari (Malahayati Nursing Journal, 2024)
ABSTRACT Nowadays healthcare industry has moved towards continuous quality improvement. Thus, health care managers must include patient-centered care activities as a major component. For this reason, patient satisfaction is a quality improvement tool for the overall performance of health facility organizations. Hospitals as health facilities must be able to realize good quality, but there is still patient dissatisfaction with hospital services, including the Prima Qonita Mother and Child Hospital (RSIA), Ogan Komering Ulu Regency, South Sumatra Province. Therefore, researchers want to focus on analyzing the hospital's outpatient satisfaction factors. Analyzing patient satisfaction factors at the RSIA Prima Qonita outpatient clinic, Ogan Komering Ulu Regency, South Sumatra Province. The method used is quantitative with a cross sectional design. The samples taken were 100 with accidental sampling techniques. The independent variables assessed were physical evidence (tangible), reliability (reliability), responsiveness (responsiveness), and assurance (assurance) and  empathy (empathy). Bivariate test using Pearson correlation test and multivariate using linear regression test. Based on the results of the Pearson Correlation test, the physical evidence factor (r= 0.193), the empathy factor (r= 0.000), the reliability factor (r= 0.318), the responsiveness factor (r= 0.000), and the assurance factor (r= 0.000) were obtained. The results of the multiple linear regression test obtained a p value of 0.249 and a coefficient B value of 57.1 for the responsiveness variable.  Each factor of empathy, responsiveness and assurance statistically influences patient satisfaction with health services at RSIA Prima Qonita inpatients. The physical evidence and reliability factors statistically have no effect on patient satisfaction with health services at the RSIA Prima Qonita inpatient facility. The most dominant factor is the responsiveness factor. Keywords: Hospital, Quality of Service, Patient Satisfaction, Tangible, Reliability, Responsiveness, Assurance, and Empathy ABSTRAK Industri pelayanan kesehatan saat ini telah bergerak menuju peningkatan kualitas yang berkelanjutan. Manajer pelayanan kesehatan harus memasukan kegiatan perawatan yang berpusat pada pasien sebagai komponen utamanya. Kepuasaan pasien menjadi alat peningkatan kualitas untuk kinerja organisasi sarana kesehatan secara keseluruhan. Rumah sakit sebagai sarana kesehatan harus mampu mewujudkan kualitas yang baik, namun masih ditemukan ketidakpuasan pasien terhadap pelayanan rumah sakit termasuk Rumah Sakit Ibu dan Anak Prima Qonita Kabupaten Ogan Komering Ulu Provinsi Sumatera Selatan.  Tujuan penelitian untuk menganalisis faktor kepuasan pasien poli rawat jalan RSIA Prima Qonita Kabupaten Ogan Komering Ulu Provinsi Sumatera Selatan. Metode yang digunakan berupa kuantitatif dengan rancangan cross sectional. Sample yang diambil sebanyak 100 dengan teknik accidental sampling. Variabel yang dinilai yaitu bukti fisik (tangible), kehandalan (reliability), daya tanggap (responsiveness), dan jaminan (assurance) dan empati (empathy). Uji bivariat menggunakan uji korelasi Pearson dan multivariat menggunakan uji regresi linearBerdasarkan hasil uji Korelasi Pearson didapatkan faktor bukti fisik (r= 0,193), faktor empati (r= 0,000), faktor kehandalan (r= 0,318), faktor daya tanggap (r= 0,000), dan faktor jaminan (r= 0,000). Hasil uji regresi linier berganda diperoleh hasil nilai p value sebesar 0,249 dan diperoleh nilai koefisien B sebesar 57,1 pada variabel daya tanggap. Masing-masing faktor empati, daya tanggap dan jaminan secara statistik berpengaruh terhadap kepuasan pasien pelayanan kesehatan di rawat inap RSIA Prima Qonita. Untuk faktor bukti fisik dan kehandalan secara statistik tidak berpengaruh terhadap kepuasan pasien pelayanan kesehatan di rawat inap RSIA Prima Qonita. Faktor yang paling dominan adalah faktor daya tanggap. Kata Kunci: Kualitas Pelayanan, Kepuasan Pasien, Tangible, Reliability, Responsiveness, Assurance, Dan Empathy